Assembly and disassembly mechanics of a spherical snap fit - Xiao-Lin Guo; Bo-Hua Sun (Theoretical and Applied Mechanics Letters, 2023)
The snap fit is a common mechanical mechanism. We have studied the spherical snap fit carefully for its physical asymmetry, which is easy to assemble but difficult to disassemble. Because of the complexity of spherical snap fit, it is difficult to get a theoretical formula to describe its physical asymmetry. In this paper, the pushing assembly and pulling disassembly of spherical snap fit are studied by both finite element analysis and experiments. The theoretical formulaes of spherical snap fit have been obtained based on numerical simulations and theoretical results of cylindrical snap fit.